Bone diagenesis and stratigraphic implications from Pleistocene karst systems - Héctor Del Valle; Alejandro B. Rodríguez-Navarro; Abel Moclán; Paula García-Medrano; Isabel Cáceres (Scientific Reports)
Abstract Bone diagenesis is a complex process that modifies bone components in response to burial conditions. These modifications help to understand deposit formation and classify fossils by stratigraphy. The combined techniques of X-ray diffraction with Rietveld refinement and infrared spectroscopy were used to study the bone diagenetic processes along the complete stratigraphic sequence of Galería site (Sierra de Atapuerca, Spain). Eleven chemometric indices considering the different bone components (phosphates, carbonates, organic phase), together with the apatite unit cell parameters and cell volume were evaluated by 9 machine learning algorithms for bone diagenesis/stratigraphic classification. The results showed differences along the stratigraphic sequence due to changes in the apatite structure chemistry (i.e., F− and OH−), producing a gradual shift of the unit cell volume (from 531.9 to 526.1 Å3) from GII to GIV associated with coupled dissolution–precipitation processes. Two diagenetic pathways are indicated: The lowest unit (GII) is characterized by leaching and carbonate loss in bone, suggesting an acidic and wet burial environment with the formation of authigenic phosphate minerals. The uppermost units (GIII-GIV) show bone apatite undergoing F− and CO3 incorporation, suggesting a slightly alkaline and drier environment. These differences enabled the development of classification models to understand deposit formation dynamics and also recontextualize dissociated fossil bones.